Vibrational spectra and normal coordinate analysis of lithium pyruvate monohydrate and its isotopic compounds - Hanai, Kazuhiko; Kuwae, Akio; Kunimoto, Ko-Ki; Kitoh, Soh-Ichi (European Journal of Chemistry, 2014)
IR and Raman spectra of lithium pyruvate monohydrate and its O- and C-deuterated and 13C- and 18O-substituted compounds have been recorded in the solid state, and the observed bands have been assigned by using the isotope effects and the normal coordinate calculations based on the gem-diol structure (lithium 2,2-dihydroxypropionate). The refined force constants have well reproduced the observed frequencies and the 13C- and 18O-shifts. These results support the structures of these compounds discussed by many authors. The potential energy distributions show that many vibrational modes are very complicated except for the well-known group vibrations. The additive property of the isotopic frequency shifts has also been discussed.